Crisis in the Reception of the Sacrament of Penance by Catholic: A Research at the Parish of Santo Paulus Pulo Brayan Bengkel Medan - Tibo, Paulinus; Simarmata, Petrus; Tamba, Krisdame (STFT Jakarta, Indonesia, 2024)
The Sacrament of Penance, according to the teachings of the Catholic Church, is a means of forgiveness of sins and restoration of a personal relationship with God. Through this sacrament, God forgives man's sins and restores his relationship with Himself. The purpose of the sacrament is not only to absolve the recipient from sin, but also to encourage them to make a strong commitment to refrain from sin in the future. The principal objective of this study is to ascertain the comprehension of Catholics regarding the sacrament of penance and Catholics' participation in receiving the Sacrament. This research focuses on the parishioners of Santo Paulus Pulo Brayan Bengkel Medan. This research employs a qualitative methodology. Data were gathered through observation of the reception of the sacrament of penance, interviews with informants to ascertain their understanding and practice of receiving the sacrament of penance, and the examination of relevant documentation. This was followed by data analysis, data reduction, data presentation, source triangulation and technique triangulation. The research reveals that Catholics have poor understanding of the sacrament of penance. The groups that are more eager to receive the Sacrament of Penance are the groups of mothers, the elderly and children. We classify these findings into the following categories: Firstly, people's understanding of the sacrament of Penance is minimal, which affects their participation in receiving the sacrament. Secondly, the implementation aspect includes both the preparation and the execution phases. The research shows that most people are not adequately prepared for confession and are not ready for its execution. This fact shows the need to educate and motivate people through catechesis so that they have a correct understanding of the importance of the sacrament of Penance.